Combined Merkel cell carcinoma and cutaneous squamous cell carcinoma with lymph node metastases: Report of two cases. (21st December 2022) - Ríos‐Viñuela, Elisa; Traves, Victor; Cruz, Julia; Machado, Isidro; López‐Guerrero, José Antonio; Requena, Celia; Llombart, Beatriz
Abstract: Merkel cell carcinoma (MCC) is an infrequent, aggressive cutaneous neoplasm, that typically affects the photodamaged skin of elderly individuals, and immunosuppressed patients. Because a subset of MCC is closely related to UV radiation, MCC can develop concurrently with other tumors, most commonly, as a combined tumor with squamous cell carcinoma (SCC). These combined tumors appear to represent a distinct disease process from pure MCC, as they are mostly Merkel cell polyomavirus (MCPyV) negative, and show a more aggressive behavior. We present two additional cases of combined MCC and SCC with nodal metastases, one of which was MCPyV positive. Two different subtypes of MCC have been proposed based on their origin: a true neuroendocrine carcinoma, that is MCPyV positive and has a dermal origin, and a UV‐related SCC with neuroendocrine differentiation. This theory could explain why MCC can develop concurrently with SCC, and why these combined cases are generally MCPyV negative. However, it fails to explain the minority of combined MCC and SCC tumors that are MCPyV positive. Because both our patients had a history of chronic UV exposure, we hypothesize that UV radiation probably played a major role in the pathogenesis of these tumors, while MCPyV integration probably acted as an additional trigger.